2018
DOI: 10.1105/tpc.18.00231
|View full text |Cite
|
Sign up to set email alerts
|

Sorbitol Modulates Resistance to Alternaria alternata by Regulating the Expression of an NLR Resistance Gene in Apple

Abstract: In plant-microbe interactions, plant sugars produced by photosynthesis are not only a carbon source for pathogens, but may also act as signals that modulate plant defense responses. Here, we report that decreasing sorbitol synthesis in apple () leaves by antisense suppression of () leads to downregulation of 56 () genes and converts the phenotypic response to from resistant to susceptible. We identified a resistance protein encoded by the apple gene and a small protein encoded by the fungal gene that interact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 104 publications
(71 citation statements)
references
References 81 publications
0
65
0
Order By: Relevance
“…However, excessive ROS can be phytotoxic (Suzuki et al, 2011). Necrotrophs are defined as pathogens that derive energy from dying or dead plant tissues, but they differ substantially in the progression of pathogenesis, ranging from rapidly killing host cells, such as Botrytis cinerea, to having an extended asymptomatic phase before killing host cells, such as Alternaria alternata (Oliver et al, 2012;Meng et al, 2018). Recently, it was suggested that suppressing PCD probably played an important role in infections by V. mali.…”
Section: Discussionmentioning
confidence: 99%
“…However, excessive ROS can be phytotoxic (Suzuki et al, 2011). Necrotrophs are defined as pathogens that derive energy from dying or dead plant tissues, but they differ substantially in the progression of pathogenesis, ranging from rapidly killing host cells, such as Botrytis cinerea, to having an extended asymptomatic phase before killing host cells, such as Alternaria alternata (Oliver et al, 2012;Meng et al, 2018). Recently, it was suggested that suppressing PCD probably played an important role in infections by V. mali.…”
Section: Discussionmentioning
confidence: 99%
“…How sorbitol is sensed and the signal is transduced to alter the expression of MdMYB39L warrants further work. As sorbitol was recently found to modulate resistance of apple leaves to Alternaria alternata by regulating the expression of an NLR gene, NLR16, via a WRKY transcription factor, WRKY79 (Meng et al, 2018b), it appears that sorbitol serves as a signal for biotic stress tolerance as well as for plant development. In light of the presence of both Glc and Suc signaling in apple (Hu et al, 2016;Liu et al, 2017), how sorbitol signaling interacts with the network of hexose/Suc signaling in sugar alcohol synthesizing species deserves further research.…”
Section: Mdstp13a Is Transcriptionally Regulated By Mdmyb39l and Mdsmentioning
confidence: 99%
“…Hu et al (2016) found that the MdSOS2L1 (coding for a calcineurin B-like protein (CBL)-interacting protein kinase, MdCIPK24-LIKE1) gene positively improved salt tolerance in apple 'Gala' by increasing the level of antioxidant metabolites such as procyanidin and malate after interaction with three calcineurin B-like proteins, MdCBL1, MdCBL4 and MdCBL10. Meng et al (2018) developed two antisense Fig. 2 Incidence of hyperhydricity in vitro and effect of gelling agent on shoot regeneration.…”
Section: In Vitro Assays For Testing Abiotic or Biotic Stress Resistancementioning
confidence: 99%